2023
DOI: 10.3389/fpls.2023.1106104
|View full text |Cite
|
Sign up to set email alerts
|

LMTdb: A comprehensive transcriptome database for climate-resilient, nutritionally rich little millet (Panicum sumatrense)

Abstract: Little millet (Panicum sumatrense) a native of Chhattisgarh, belongs to the minor millet group and is primarily known as a climate-resilient and nutritionally rich crop. However, due to the lack of enough Omic studies on the crop, the scientific community has largely remained unaware of the potential of this crop, resulting in less scope for its utilization in crop improvement programs. Looking at global warming, erratic climate change, nutritional security, and limited genetic information available, the Littl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Protein BLAST analysis and Pfam analysis showed that Sobic.003G010300 encodes an SbCYP71A1 protein, which belongs to the Cytochrome P450 superfamily (CYP) (Figure 4A). Homology alignment and gene annotation revealed that the CYP71A1 gene codes for the tryptamine 5-hydroxylase enzyme (Figure 4B), a crucial component in the plant serotonin/melatonin biosynthesis pathway [30,31]. This confirmed that Sobic.003G010300 is a potential candidate gene for sblob1.…”
Section: Identification and Validation Of Candidate Gene Accounting F...mentioning
confidence: 57%
“…Protein BLAST analysis and Pfam analysis showed that Sobic.003G010300 encodes an SbCYP71A1 protein, which belongs to the Cytochrome P450 superfamily (CYP) (Figure 4A). Homology alignment and gene annotation revealed that the CYP71A1 gene codes for the tryptamine 5-hydroxylase enzyme (Figure 4B), a crucial component in the plant serotonin/melatonin biosynthesis pathway [30,31]. This confirmed that Sobic.003G010300 is a potential candidate gene for sblob1.…”
Section: Identification and Validation Of Candidate Gene Accounting F...mentioning
confidence: 57%
“… [ 3 ] For the climate-resistant, nutrient-dense little millet, a thorough transcriptome database was discovered. [ 52 ] Foxtail millets Genome sequencing was used to assess the resistance to biotic stress in foxtail millet. [ 53 ] RIL population and widely targeted metabolome were used to conduct QTL analysis of significant agronomic characteristics and metabolites in foxtail millet.…”
Section: Prospects Of Millet Cultivation In Bangladeshmentioning
confidence: 99%